Human papillomavirus genotypes in cervical and other HPV‐related anogenital cancer in Rwanda, according to HIV status. Issue 6 (26th June 2019) - Mpunga, Tharcisse; Chantal Umulisa, Marie; Tenet, Vanessa; Rugwizangoga, Belson; Milner Jr, Danny A.; Munyanshongore, Cyprien; Heideman, Daniëlle A.M.; Bleeker, Maaike C.G.; Tommasino, Massimo; Franceschi, Silvia; Baussano, Iacopo; Gheit, Tarik; et al.
Abstract : The study aim was to describe human papillomavirus (HPV)‐attributable cancer burden in Rwanda, according to anogenital cancer site, HPV type, age and HIV status. Tissue specimens of cervical, vulvar, vaginal, penile and anal cancer diagnosed in 2012–2018 were retrieved from three cancer referral hospitals and tested for high‐risk (HR) HPV DNA. Cervical cancer represented the majority of cases (598 of 738), of which 96.0% were HR‐HPV positive. HPV‐attributable fractions in other cancer sites varied from 53.1% in 81 penile, through 76.7% in 30 vulvar, 83.3% in 24 vaginal, up to 100% in 5 anal cases. HPV16 was the predominant HR‐HPV type in cervical cancer (55.0%), followed by HPV18 (16.6%) and HPV45 (13.4%). HPV16 also predominated in other cancer sites (60–80% of HR‐HPV‐attributable fraction). For cervical cancer, type‐specific prevalence varied significantly by histology (higher alpha‐9 type prevalence in 509 squamous cell carcinoma vs . higher alpha‐7 type prevalence in 80 adenocarcinoma), but not between 501 HIV‐negative and 97 HIV‐positive cases. With respect to types targeted, and/or cross‐protected, by HPV vaccines, HPV16/18 accounted for 73%, HPV31/33/45/52/58 for an additional 22% and other HR‐HPV types for 5%, of HPV‐attributable cancer burden, with no significant difference by HIV status nor age. These data highlight the preventive potential of the ongoing national HPV vaccination program in Rwanda, and in sub‐Saharan Africa as a whole. Importantly for this region, the impact of HIV on the distribution of causal HPV types was relatively minor, confirming type‐specific relevance of HPV vaccines, irrespective of HIV status. Abstract : What's new? Sub‐Saharan Africa suffers the highest cervical‐cancer rates in the world, due in part to a lack of cervical‐cancer screening programs. In 2011, Rwanda initiated a national HPV‐vaccination program, achieving >90% coverage. In this study, the authors characterized the subsequent burden of all forms of anogenital cancer attributable to high‐risk (HR) HPV types, including cervical, anal, etc. These results illustrate the preventive potential of a national HPV‐vaccination program. They also enhance our understanding of the HPV‐attributable fraction of non‐cervical anogenital cancers in sub‐Saharan Africa overall.